Perjalanan Spiritual Orang Berilmu dalam Al-Quran: Studi Analisis Surah Ali Imran, Al-‘Ankabut, dan Az-Zumar - Amrina Rasyada; Maulana, Dafit; Salsabila, Fina; Rahmawati, Ana (Institut Darul Quran Payakumbuh, 2025)
The spiritual journey in Islam is a process of drawing closer to Allah SWT by increasing awareness and understanding. For people of knowledge, it involves not only seeking knowledge but also deepening their comprehension of life and creation. Through contemplation, observing nature, and applying knowledge, they feel a closer connection to God. This research examines the spiritual journey through Surah Ali Imran: 190-191, Al-Ankabut: 43, and Az-Zumar: 18, focusing on interpretations by renowned scholars. Using a thematic approach, it analyzes Qur’anic verses with similar themes, supported by relevant literature. The findings highlight three key aspects of the journey: (1) linking natural observations with divine consciousness, (2) deep understanding of knowledge, and (3) wisdom in applying it. Knowledgeable individuals do not merely acquire information but seek deeper meaning and wisely practice what they learn. This study affirms that knowledge and spirituality in Islam are interconnected, guiding individuals to a life of greater meaning and a closer relationship with Allah SWT. The spiritual journey merges knowledge with reflection, helping individuals grow closer to God through understanding and wise application.